1996
DOI: 10.1093/geront/36.5.649
|View full text |Cite
|
Sign up to set email alerts
|

Does Retirement Hurt Weil-Being? Factors Influencing Self-Esteem and Depression Among Retires and Workers

Abstract: A set of older workers from the Raleigh-Durham-Chapel Hill metropolitan area were followed for two years in order to explore the social psychological consequences of retirement. Three findings are of particular interest. First, when we separated workers who retired from those who continued to work and compared their self-esteem and depression scores over the two-year interval, we found that self-esteem scores did not change for either group, but that depression scores declined for workers who retired. Turning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
1
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 27 publications
2
88
1
7
Order By: Relevance
“…Although previous studies such as the one by Bossé et al [20] have not found differences in psychological symptoms between retirees and workers, others have reported improved mental health and emotional aspects in retirees who held some kind of occupation after retirement [21] and a worsening in mental health in inactive retirees [22]. The general analysis of data in the present research revealed a strong presence of positive aspects of being retired reported by the respondents.…”
Section: Discussioncontrasting
confidence: 47%
“…Although previous studies such as the one by Bossé et al [20] have not found differences in psychological symptoms between retirees and workers, others have reported improved mental health and emotional aspects in retirees who held some kind of occupation after retirement [21] and a worsening in mental health in inactive retirees [22]. The general analysis of data in the present research revealed a strong presence of positive aspects of being retired reported by the respondents.…”
Section: Discussioncontrasting
confidence: 47%
“…Gonzáles et al (1995) 22 relataram piora na saúde mental em aposentados inativos. Reitzes et al (1996) 23 também observaram melhora da saúde mental e dos aspectos emocionais em aposentados que mantinham algum tipo de ocupação após a aposentadoria. Herzog et al (1991) ressaltaram que a forma de exercício da atividade de trabalho após a aposentadoria pode influir na qualidade de vida, destacando que o trabalho estressante contribuiu para uma piora da saúde mental em aposentados 24 .…”
Section: Discussionunclassified
“…Reitzes et al 1996) Demographic trends mean that older workers form an increasing proportion of the workforce. Some reduction in physical and mental capability and workability is probably inevitable with age, but chronological age is not a reliable marker.…”
Section: (B) the Health Impact Of Early Retirementmentioning
confidence: 99%